A classification framework for clinical information system implementation in hospitals. (1st January 2012) - Meulendijks, Arjan; Batenburg, Ronald; van de Wetering, Rogier
In the last decade, many information system (IS) implementations took place in the healthcare organisations. Mainstream reasons for this evolvement are the increase of quality and safety of care, and reducing costs. As in many other sectors IS implementations in healthcare are complex, and confronted with many types of difficulties that significantly hinder achieving the objected benefits. So far, a number of systematic overviews and classifications of critical success factors (CSFs) have been available for IS implementation in healthcare, but a CSF framework specifically for clinical information systems (CISs) in hospitals does not exist. This paper provides such a framework, validates it, and translates it into a practical contribution for IT project managers in hospitals. The framework is based on a systematic literature review that has been performed to extract relevant SCFs from recent academic publications. After a filtering process, 58 publications have been selected from which 248 success factors have been extracted. Building upon seven existing classifications, the classification framework for CSFs in CIS implementations was build. Expert interviews were conducted to validate the framework and the relative weights of eight CSF categories.